Forced Marriage In The Perspective Of Islamic Law In Bacem Village Sutojayan District, Blitar District - M. Firdaus Alwi Mahbubi; Ahmad Hafidz Safrudin (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2022)
Marriage is a sunnah of Rasulullah SAW, although there are also marriages that are carried out by forcing children to marry someone of the parents' choice. This happened in the village of Bacem, Sutojayan sub-district, Blitar district. In this society, if we look closely at the objects (children), they are sometimes dissatisfied with their parents' choices. On the other hand, if their children choose their own life partners, the parents do not approve of that choice, and the parents may try to hinder their children's relationships with material and non-material pressures. So it seems that children do not have the right to choose the life partner they want. In this case, the practice of forced marriage is that most children are without consideration and are immediately married off by their guardians, and because the environment is religious and most understand or are knowledgeable about religion, they do not want to disappoint their parents and family and in the end they choose to obey their parents and try to understand each other even though it takes a long time to maintain their household. While the impact of forced marriage in general is the need for a long adaptation to understand each other to achieve the goals of marriage. The practice of forced marriage of this kind when viewed from the perspective of Islamic law is still valid according to the Imam Syafi'i school of thought, but is accompanied by various requirements.